1988
DOI: 10.2307/3676532
|View full text |Cite
|
Sign up to set email alerts
|

Badge, Body and Testes Size in House Sparrows Passer domesticus

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
1

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(13 citation statements)
references
References 10 publications
1
11
1
Order By: Relevance
“…A positive correlation has been found between testes volume (an indirect measure of T concentrations) and badge size [Møller and Erritzoe, 1988]. Direct manipulations and measurements of T concentrations have confirmed that development of badge size is influenced by T concentrations [Evans et al, 2000;Buchanan et al, 2001;Gonzalez et al, 2001].…”
Section: Introductionmentioning
confidence: 79%
“…A positive correlation has been found between testes volume (an indirect measure of T concentrations) and badge size [Møller and Erritzoe, 1988]. Direct manipulations and measurements of T concentrations have confirmed that development of badge size is influenced by T concentrations [Evans et al, 2000;Buchanan et al, 2001;Gonzalez et al, 2001].…”
Section: Introductionmentioning
confidence: 79%
“…First, plumage characters should be correlated signi¢cantly with indices of quality, such as phenotypic condition, size, testes volume and age (Kodric-Brown & Brown 1984;MÖller & ErritzÖe 1988;Andersson 1992;Hill 1992;Jones & Montgomerie 1992;Andersson 1994;Hill & Montgomerie 1994;MÖller 1994;Veiga & Puerta 1996;Gri¤th et al 1999). Second, expression of characters should have a high degree of environmental determination (Kodric-Brown & Brown 1984;Hill 1992;Andersson 1994;MÖller 1994;Gri¤th et al 1999) since environmental e¡ects (like quality of diet or exposure to disease) should strongly in£uence an individual's overall quality.…”
Section: (A) Predictionsmentioning
confidence: 99%
“…Second, expression of characters should have a high degree of environmental determination (Kodric-Brown & Brown 1984;Hill 1992;Andersson 1994;MÖller 1994;Gri¤th et al 1999) since environmental e¡ects (like quality of diet or exposure to disease) should strongly in£uence an individual's overall quality. Third, each plumage character should have a unimodal frequency distribution (this is not an absolute requirement for a quality indicator, however unimodal distributions are almost always observed in indicator traits in other species (MÖller & ErritzÖe 1988;Andersson 1992;Hill 1992;MÖller 1994;Wolfenbarger 1999;see Senar (1999) for an exception) and they presumably arise from unimodal distributions in the overall quality underlying the traits). Fourth, di¡erent plumage characters should be positively correlated with one another (Kodric-Brown & Brown 1984; Hill 1992; Camplani et al 1999) (this prediction assumes that the di¡erent characters re£ect, at least in part, some common aspects of quality (such as overall vigour)).…”
Section: (A) Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…In theory, males of a given species that invest most into secondary sexual trait expression may be of highest phenotypic condition in the population as a result of their superior ability to acquire and assimilate resources for allocation to competing physiological functions (Rowe and Houle 1996;Bonduriansky and Rowe 2005). By extension, males sporting the most welldeveloped ornaments may also be those able to invest most into ejaculate quality and associated structures (e.g., testes; Møller and Erritzoe 1988;Sheldon 1994). In D. bipectinata, because the male sex comb is composed of rows of stout, melanized teeth (modified bristles), internally made up of structural protein (actin) filaments (Tilney et al 2000), variation in ornament size may reveal individual feeding history, and their ability to accumulate body supplies of critical amino acids and other essential nutrients, thereby driving an association between ornament size and ejaculate quality (see also Amitin and Pitnick 2007).…”
Section: Discussionmentioning
confidence: 99%